Peningkatan Motivasi Kerja Guru Melalui Supervisi Klinis di SDN 12/X Pemusiran Pada Semester Ganjil Tahun Ajaran 2021/2022 - Lilis Suryani (Journal on Education, 2023)
This research is motivated by the teacher's work motivation in carrying out learning which still needs to be improved. This study aims to discuss and obtain information about increasing teacher motivation through clinical supervision at SDN 12/X Pemusiran in the odd semester of the 2021/2022 academic year. This type of research is school action research. This research was conducted at SDN 12/X Pemusiran in the odd semester of the 2021/2022 academic year. The research subjects were all teachers at SDN 12/X Pemusiran, totaling 5 people. Data was collected through observation sheets, field notes, and documentation. Data analysis techniques use percentages and data reduction. Based on the results of the research and discussion that has been carried out by the teacher, it can be concluded that the work motivation of SDN 12/X Pemusiran teachers increased from cycle I to cycle II through clinical supervision conducted by the school principal. This can be seen from the completeness of each assessment indicator carried out by the teacher as well as by class visits and rewards.